Gold Prospects in the Western Segment of the Russian Arctic: Regional Metallogeny and Distribution of Mineralization - Arkady A. Kalinin; Oleg V. Kazanov; Vladimir I. Bezrukov; Vsevolod Yu. Prokofiev (Minerals, 2019)
Location of the deposits and occurrences of gold mineralization in metamorphic complexes of the Kola region is controlled by tectonic zones at the regional scale at the boundaries of major segments of the Fennoscandian Shield. Three zones are the most important: (1) the system of Neoarchean greenstone belts Kolmozero–Voron’ya–Ura-guba along the southern boundary of the Murmansk craton; (2) the suture, delineating the core of the Lapland–Kola orogeny in the north; and (3) the series of overthrusts and faults at the eastern flank of the Salla–Kuolajarvi belt. Gold deposits and occurrences are located within greenstone belts of Neoarchean and Paleoproterozoic age, and hosted by rocks of different primary compositions (mafic metavolcanics, diorite porphyry, and metasedimentary terrigenous rocks). The grade of metamorphism varies from greenschist to upper amphibolite facies, but the mineralized rocks are mainly lower amphibolite metamorphosed, close to the transition from greenschist to amphibolite facies. Gold deposits and occurrences in the northeastern part of the Fennoscandian Shield formed during two periods: the Neoarchean 2.7–2.6 Ga and the Paleoproterozoic 1.9–1.7 Ga. According to paleo-geodynamic reconstructions, these were the periods of collisional and accretionary orogeny in the region. Those Archean greenstone belts, which were reworked in the Paleoproterozoic (e.g., Strel’na and Tiksheozero belts), can contain gold deposits of Paleoproterozoic age.